Community Empowerment: Enhancing the Role of Families in Dealing with Domestic Conflicts - Syafingi, Habib Muhsin; Hakim, Hary Abdul; Meivialora, Meivialora; Fianto, Ardi Kusna; Prayoga, Aryudha Ilham Ramadhan; Mukti, Krisna (Universitas Muhammadiyah Magelang, 2025)
Domestic conflict is a social phenomenon inseparable from the dynamics of family life and has the potential to disrupt family harmony and functioning if not managed constructively. This study aims to analyze the increasing role of families in managing domestic conflict with stress on the experiences, meanings, and social processes experienced by family members. The study used a qualitative approach with a phenomenological method to explore the lived experiences of families in managing domestic conflict. Data were collected through in-depth semi-structured interviews, limited observations, and supporting documentation of families who have experienced or are currently experiencing domestic conflict in the Mertoyudan area. Research participants were selected purposively with the criteria of direct involvement in the conflict resolution process. The results show that domestic conflict is understood as a relational process that develops gradually, influenced by economic pressures, ineffective communication, and emotional accumulation. These findings strengthen the perspective of family systems theory and family resilience by positioning the family as an active subject in conflict management. This research highlights the importance of strengthening internal family capacity through family-based communication and conflict resolution education.